2020
DOI: 10.7717/peerj.10480
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing FDA-approved phytomedicines, natural products, antivirals and cell protectives against SARS-CoV-2 (COVID-19) RNA-dependent RNA polymerase

Abstract: Following the recent emergence of SARS-CoV-2 or coronavirus disease 2019 (COVID-19), drug discovery and vaccine design to combat this fatal infection are critical. In this study, an essential enzyme in the SARS-CoV-2 replication machinery, RNA-dependent RNA polymerase (RDRP), is targeted in a virtual screening assay using a set of 1,664 FDA-approved drugs, including sets of botanical and synthetic derivatives. A set of 22 drugs showed a high docking score of >−7. Notably, approximately one-third of the top … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 20 publications
(19 reference statements)
0
26
0
Order By: Relevance
“…Pro168, His41, and Val116 residues contact probabilities between demethoxycurcumin-Mpro and bisdemethoxycurcumin-Mpro decreased (Table 3). Previous studies have shown COVID-19 main protease possesses a dynamic binding pocket loop comprising domain-I (residues 10-99) and domain-II (residues 100-184), in which most of the residues in this study laid (Jin et al, 2020;Kouznetsova et al, 2020;Kandeel, Kitade & Almubarak, 2020).…”
Section: Discussionmentioning
confidence: 73%
“…Pro168, His41, and Val116 residues contact probabilities between demethoxycurcumin-Mpro and bisdemethoxycurcumin-Mpro decreased (Table 3). Previous studies have shown COVID-19 main protease possesses a dynamic binding pocket loop comprising domain-I (residues 10-99) and domain-II (residues 100-184), in which most of the residues in this study laid (Jin et al, 2020;Kouznetsova et al, 2020;Kandeel, Kitade & Almubarak, 2020).…”
Section: Discussionmentioning
confidence: 73%
“…Several studies have demonstrated the efficacy of phytochemicals, such as flavonoids, anisotine, and other natural molecules, for the treatment of COVID-19 infection [ [18] , [19] , [20] , [21] , [22] ]. A recent study reports the RdRp inhibitory potential of FDA-approved phytochemicals that can be used to treat COVID-19 [ 23 ]. In the present study, we aimed to screen plant-based natural molecules (approximately 1064) for their inhibitory effects against RdRp and Mpro using an in silico molecular docking approach.…”
Section: Introductionmentioning
confidence: 99%
“…Theaflavins, neohesperidin, naringenin, echinacoside, and salvianolic acid inhibited RNA-dependent RNA polymerase activity, blocking the active site of the groove (an active site for the polymerization of RNA but distal from the active site) through hydrophobic and hydrogen interactions [ 223 , 224 ]. Epigallocatechin gallate, theaflavin, and rutin digallate also show interactions with SARS-CoV-2 3CLpro, SARS-CoV-2 spike protein, and ACE2 receptor through a combination of hydrogen bonding, van der Waals and other hydrophobic interactions [ 225 , 226 ].…”
Section: Mechanisms Of Antioxidants Compounds Against Sars-cov-2 In Covid-19mentioning
confidence: 99%
“…Other proposed candidates as neuroprotectors in patients with COVID-19 for their antioxidant capacity are: salicyl-carnosine [ 288 ], molecular hydrogen [ 224 ], cannabinoid type-2 receptor-selective agonists [ 289 ], propolis [ 290 ], thymoquinone, nigellidine, and α-hederin [ 291 ], agomelatine [ 292 ], and ozone [ 293 ].…”
Section: Antioxidants As Neuroprotectors In Patients Infected With Covid-19mentioning
confidence: 99%